URGENSI MANAJEMEN DALAM BISNIS ISLAM - Riyadi, Fuad (BISNIS, 2015)
In Islamic business, management serve as the basic elements that lways exist and attached to the business processes that will be used as eference by managers in carrying out activities to achieve goals. Urgency of management in a business that is designed includes five functions: planning (planning), organizing (organizing), actuating (mobilization),controlling (control), evaluating (evaluation), coordinating(coordination), motivating (motivation) and leading (leadership). Sothere are seven function from the management perspective of Islam.Business in Islam also aims to achieve four main things: (1) the targetresults: profit-material and non-material benefits, (2) growth, (3)sustainability, (4) blessing.